How Russia is recruiting for the long war: Covertly mobilising volunteers while preparing for a new round of compulsory mobilisation - Margarete Klein (Stiftung Wissenschaft und Politik (SWP), 2024)
In its war of attrition against Ukraine, the Kremlin is counting on outnumbering the enemy over a long period in terms of both hardware and personnel. Following the unpopular partial mobilisation in autumn 2022, the recruitment of contract soldiers and volunteer fighters was stepped up significantly in order to conceal the human costs of war. At the same time, the 'Wagner mutiny' showed that the diffusion of the structures of violence as part of the covert mobilisation poses risks for the regime. For this reason, control over the volunteer formations has been tightened, while the Kremlin is laying the groundwork for a new round of compulsory mobilisation. However, Russia is not only recruiting for the war against Ukraine; the plan to increase the number of soldiers to 1.5 million clearly shows that the Kremlin is preparing for a prolonged confrontation with the West..
Keywords: 320; Vladimir Putin; Yevgenii Prigozhin; Defence Minister Sergei Shoigu; Russia; war against Ukraine; militarisation of Russian foreign policy; "compulsory mobilisation"; National Guard; soldiers; Cossacks; reservists; conscripts; volunteers; mobiki; kontraktniki; private military companies (PMCs); partial mobilisation; confrontation with the West; number of casualties; Georgia; Crimea; Donbas; NATO; EU